REPRESENTATION OF METAPHORS IN LITERARY TRANSLATION: A STUDY BASED ON THE WORKS OF OSCAR WILDE - Khamidova Nigina Mirkhodiyevna (American Journals Publishing, 2025)
Metaphor is an essential stylistic device in literary texts, functioning both semantically and pragmatically to convey imagery, ideology, and authorial voice. Translating metaphors presents a particular challenge because metaphors are culture-bound, lexically varied, and tightly integrated with a text’s tone and register. This article explores strategies for representing metaphors in literary translation, using selected passages from Oscar Wilde’s major works as case studies. By combining theoretical perspectives from translation studies and cognitive metaphor theory with close textual analysis, the paper argues for a flexible, context-sensitive approach: translators should balance fidelity to source metaphors with target-language naturalness, and choose strategies (literal transfer, modulation, paraphrase, compensation, or creative replacement) that preserve functional and aesthetic effects rather than surface forms. Implications for translator training and for machine-augmented translation are discussed.
Keywords: Metaphor, lexical/ figurative form, conceptual compatibility, pragmatic work, conventional mapping, comparative analysis, index speaker, multifunctionality